2022
DOI: 10.3389/fphar.2022.835727
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Circulating Tumor Cell Enumeration: Cell-Based Liquid Biopsy to Assess Protein Biomarkers and Cancer Genomics Using the RareCyte® Platform

Abstract: The practice of medicine has steadily employed less invasive methods to obtain information derived from the tumor to guide clinical management of patients. Liquid biopsy—the sampling of blood—is a non-invasive method for generating information previously only available from tissue biopsies of the tumor mass. Analysis of fragmented circulating tumor DNA in the plasma is clinically used to identify actionable mutations and detect residual or recurrent disease. Plasma analysis cannot, however, assess cancer pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In this method, CTCs are isolated from whole blood, applied to a slide, stained with specific immunofluorescent dyes, and analyzed via automated microscopic imaging with an integrated fluid-coupled picking system for single-cell retrieval. Kaldjian et al reported that the rate of successful CTC retrieval using this method was 80%–90% [ 25 ] and subsequently showed that the retrieved cells can be used for tumor characterization based on tumor-specific protein biomarkers [ 11 ].…”
Section: Current Enrichment and Detection Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, CTCs are isolated from whole blood, applied to a slide, stained with specific immunofluorescent dyes, and analyzed via automated microscopic imaging with an integrated fluid-coupled picking system for single-cell retrieval. Kaldjian et al reported that the rate of successful CTC retrieval using this method was 80%–90% [ 25 ] and subsequently showed that the retrieved cells can be used for tumor characterization based on tumor-specific protein biomarkers [ 11 ].…”
Section: Current Enrichment and Detection Techniquesmentioning
confidence: 99%
“…The molecular characterization of CTCs, which will play a central role in evolving methods for CTC detection, has the potential to unravel the biology of tumor evolution and resistance and to shed new light on cancer progression at the genomic, transcriptomic, proteomic, and metabolic levels [ 6 , 9 , 10 ]. Moreover, detecting actionable variants that have not been identified in the primary tumor can help to guide treatment [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional biomarkers may also be relevant to a specific tumor subtype, provide prognostic value, or to facilitate patient selection for targeted therapies. For example, PD-L1 for monitoring patients undergoing immunotherapy ( 10 ), androgen receptor splice variant 7 (ARv7) for emergence of therapeutic resistance in prostate cancer ( 31 ), and assessing biomarkers such as EGFR, HER2 or PD-L1 in esophageal cancer ( 36 ). Furthermore, the platform has a single-cell retrieval device, CellPicker™, where identified cells can be picked for single-cell molecular characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the platform has a single-cell retrieval device, CellPicker™, where identified cells can be picked for single-cell molecular characterization. This includes genomic analysis such as TP53 mutations in breast cancer cells ( 27 ), APC mutations in colorectal cancer ( 36 ), targeted mutational panels in prostate ( 31 ) and lung cancer ( 33 ); and single-cell RNA sequencing as demonstrated in breast cancer ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the heterogeneity, the fact that resistant clones of tumors may represent only a small proportion of the entire tumor and are unlikely to suffer apoptosis, the genomes of resistant tumor subclones may not be detectable at the current sensitivity limits of cell-free DNA assays. As intact cancer cells that have entered the blood, CTCs show the predictive capability of the response to drugs through analyzing protein biomarkers on CTCs and show the broad detection of mutations through genome-wide sequencing ( 22 ). CTCs are identified and sequenced to identify operable mutations in drug-resistant subclones that are not present in the majority of tumors to guide subsequent therapy.…”
Section: Discussionmentioning
confidence: 99%